2002
DOI: 10.1128/aac.46.6.1805-1815.2002
|View full text |Cite
|
Sign up to set email alerts
|

Quinolone-Binding Pocket of DNA Gyrase: Role of GyrB

Abstract: DNA gyrase is a prokaryotic type II topoisomerase and a major target of quinolone antibacterials. The majority of mutations conferring resistance to quinolones arise within the quinolone resistance-determining region of GyrA close to the active site (Tyr 122 ) where DNA is bound and cleaved. However, some quinolone resistance mutations are known to exist in GyrB. Present structural data suggest that these residues lie a considerable distance from the quinolone resistance-determining region, and it is not obvio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 48 publications
3
91
0
Order By: Relevance
“…The antibacterial fluoroquinolones have been found to be one of the fastest growing groups of drugs in recent years [5][6][7][8] . Quinolones are known for their antibacterial and antitumor activities through alteration of the normal functions of bacterial gyrase, and are found to be a topoisomerase II inhibitor in humans [9][10][11][12][13][14][15][16][17][18] . Ciprofloxacin (Figure 1), a commonly used broadspectrum fluoroquinolone antibiotic, has shown anticancer activity in several cancer cell lines 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial fluoroquinolones have been found to be one of the fastest growing groups of drugs in recent years [5][6][7][8] . Quinolones are known for their antibacterial and antitumor activities through alteration of the normal functions of bacterial gyrase, and are found to be a topoisomerase II inhibitor in humans [9][10][11][12][13][14][15][16][17][18] . Ciprofloxacin (Figure 1), a commonly used broadspectrum fluoroquinolone antibiotic, has shown anticancer activity in several cancer cell lines 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their effect on quinolone sensitivity, mutations at sites D426 and K447 also inhibit the gyrase catalytic activity (13). It has been proposed that the quinolone-binding site is a pocket surrounded by surfaces involving the quinolone resistance-determining regions of both the GyrA and GyrB proteins (13,27).Isolation of the gyrB651 allele and its phenotypic suppressor, gyrA659. Mutants of Salmonella enterica serovar Typhimurium resistant to low levels of nalidixic acid were isolated by plating 0.2 ml of an overnight liquid culture from strain MA251 (Table 1) on nutrient broth (Difco) agar containing 3 g/ml Nal.…”
mentioning
confidence: 99%
“…According with our results, biochemistry research [32] indicated that, norfloxacin almost did not bind with gyrase or DNA when only one of them existed; but a large number of norfloxacin was bound if both existed. Moreover, biochemistry research [33] and crystal structure [34] showed that norfloxacin together with DNA and gyrase formed a stable complex where norfloxacin bound near active site of GyrA Tyr122 and interact with GyrB and DNA. Besides, gyrase could change the geometric scale of DNA supercoils, yielding chiral differences, clearly indicating that it has different effects on positive and negative supercoils.…”
Section: Discussionmentioning
confidence: 99%